Vegetable oil as fuel for diesel engines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
There is little new about the idea of using vegetable oil as engine fuel, but for a long time technical problems and the low price of petroleum-based fuels have meant that the idea has not been pursued in practice. However, a German project in Mali...